2017
DOI: 10.1186/s12941-017-0242-9
|View full text |Cite
|
Sign up to set email alerts
|

Coagulase gene polymorphism, enterotoxigenecity, biofilm production, and antibiotic resistance in Staphylococcus aureus isolated from bovine raw milk in North West India

Abstract: Background Staphylococcus aureus is the predominant bacterium responsible for various diseases in animals and humans. Preventive strategies could be better implemented by understanding the prevalence, genetic patterns, and the presence of enterotoxin and biofilm-producing genes along with the antibiotic susceptibility of this organism. This study was conducted in Rajasthan, the northwestern state of India, holding the largest population of cattle that makes it the second largest milk producer in India and no s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
32
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 45 publications
10
32
2
4
Order By: Relevance
“…In this study, our findings are in agreement with Tang, Chen, Li, Zeng, and Li (2013), who observed that contributions of adhesion genes vary greatly within strains. Among 15 MSCRAMMS tested genes, eno (96%), clfB (94%), and icaBC (94%) genes were found at a high prevalence and our results are in accordance with the findings of Tang et al (2013) and Sharma et al (2017). The eno gene encodes a laminin binding protein which is expressed on the surface of S. aureus.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, our findings are in agreement with Tang, Chen, Li, Zeng, and Li (2013), who observed that contributions of adhesion genes vary greatly within strains. Among 15 MSCRAMMS tested genes, eno (96%), clfB (94%), and icaBC (94%) genes were found at a high prevalence and our results are in accordance with the findings of Tang et al (2013) and Sharma et al (2017). The eno gene encodes a laminin binding protein which is expressed on the surface of S. aureus.…”
Section: Discussionsupporting
confidence: 89%
“…() and Sharma et al. (). The eno gene encodes a laminin binding protein which is expressed on the surface of S. aureus .…”
Section: Discussionmentioning
confidence: 98%
“…Among the 120 isolates analyzed, only 17 (14%) were not enterotoxigenic (1 from Argentina, 1 from Colombia, 2 isolates from Germany, 3 from Italy, 1 from New York State, 1 from South Africa, and 8 from Tunisia). The remaining 103 isolates (86%) harboured a combination of at least 2 up to 5 enterotoxins with the linkages between sea , sed , seg and seh confirming their predominance in cows, as previously described [ 21 , 22 , 23 , 24 ]. The absence of the enterotoxin genes seb and see in our isolates was in accordance with previous results [ 15 , 22 , 25 , 26 ].…”
Section: Discussionsupporting
confidence: 79%
“…The current study highlights the prevalence of antibiotic‐resistant STEC serogroups in the northern regions of India, other studies have also reported the prevalence of other antibiotic resistance foodborne pathogens, Staphylococcus aureus , Listeria monocytogenes , and Campylobacter jejuni (Khan et al, ; Sharma et al, , ), within the food chain in the north India, which further highlight the significance and importance of controlling the use of antibiotics in agriculture, as well as improving the hygiene practices in public and the food industry.…”
Section: Discussionsupporting
confidence: 56%
“…Staphylococcus aureus, Listeria monocytogenes, and Campylobacter jejuniSharma et al, 2017aSharma et al, , 2017b, within the food chain in the north India, which further highlight the significance and importance of controlling the use of antibiotics in agriculture, as well as improving the hygiene practices in public and the food industry.…”
mentioning
confidence: 98%